Optimizing after-sales services in the automotive maintenance sector: a lean manufacturing and MRP case study in Peru - Harboe Chaman, Pablo Andres (2025)
The objective of this research is to improve productivity and increase customer satisfaction in the automotive maintenance sector in Peru, which faces problems such as inefficient after-sales services and poor inventory management. The methodology proposes the integration of lean manufacturing tools such as: 5S, material requirements planning, standard work, among others. The implementation of these tools seeks to optimize the organization of the workspace, improve inventory management and turnover, and streamline after-sales service operations. The main results were a 20.37% reduction in downtime, a decrease in stockouts from 11.81% to 3.58%, and a reduction in cycle time from 3 hours and 15 minutes to 1 hour and 36 minutes. These advances contributed to a significant increase in customer satisfaction, reflected in an increase in NPS from 46% to 79%. It is suggested that the use of digital technologies such as IoT and AI be explored to continue improving.